Cell‐Free and Concentrated Ascites Reinfusion Therapy for Refractory Ascites Following Pediatric Liver Transplantation - Itsuki Naya; Naoya Yamada; Yoshihiro Hirata; Yoshiyuki Ihara; Megumi Tamura; Motoki Ebihara; Shoichi Tsuzaka; Rina Matsuda; Shotaro Taki; Shoko Ogawa; Kyoichi Deie; Hiroshi Kawashima; et al. (Therapeutic Apheresis and Dialysis, 2026)
ABSTRACT Introduction Cell‐free and concentrated ascites reinfusion therapy (CART) has been widely used for malignant ascites and decompensated cirrhosis, but its perioperative application remains unclear. We evaluated CART after pediatric living donor liver transplantation (LDLT). Methods We retrospectively reviewed pediatric LDLT recipients who underwent CART for refractory ascites. Changes in ascites volume, protein recovery rates including albumin and immunoglobulin G (IgG), and adverse events were analyzed. Results Ten recipients underwent 92 CART sessions. Median ascites volume decreased from 1785 mL to 362 mL after concentration. Median recovery rates were 70.1% for total protein, 71.8% for albumin, 72.0% for IgG, 76.2% for antithrombin III, and 109.4% for coagulation factor XIII. Larger ascites volumes were weakly associated with higher recovery efficiency. No serious adverse events occurred. Conclusions CART may be a safe and useful option for managing refractory ascites and protein recovery after pediatric LT while minimizing reinfusion volume.